A new Hygrochroma Herrich-Schäffer (Geometridae: Ennominae) from Mexico City named by its residents after an ancient volcano - Garzón-Orduña, Ivonne J. (Zootaxa, 2023)
A new species of Hygrochroma Herrich-Schäffer is described and illustrated from a male and two females deposited in Mexico’s National Insect Collection. Hygrochroma xitle Garzón-Orduña sp. n. is distinguished from other Hygrochroma by its two, bold, longitudinal white lines on the ventral surface of the wings. The species name was chosen by a crowd-sourced initiative that presented the general public with five alternative names. Xitle, the name of an ancient volcano located inside Mexico City, was the most popular, winning over the others with 1,881 votes.